ETOS KERJA PANDANGAN DUNIA PENGANGKUT SAMPAH - Sariyatun Sariyatun (Universitas Sebelas Maret, 2009)
The main problem of this research is to answer the following questions: are thereanyfactorsinfluencing:levelofeffectiveworkingmodelandviewsofgarbageman. The main objective of this research is to reveal the effective working model and the garbageman's view on work ethic. The number of research respondents is 200 garbagemen in Surakarta determined by using cluster random sampling. The research data were obtained by using questionnaire and then they were analyzed by using regression and linear analyses. The results of the research showed that: (1) There was no significantly positive direct effect towards the income standard on the level of effective working motivation and working satisfaction; (2) There was a significantly positive direct effect towards working model and garbageman's view on effective working motivation and effective contribution (1,93%); (3) There was a significantly positive effective effect towards working model and garbageman's view on the factors of working satisfaction level and effective contribution (2,47%); (4) There was a significantly positive effect towards working model and garbageman's view on the factors of living standard and effective contribution (6,17%); (5) There was no direct effect towards workingmodelandgarbageman'sviewonthefactorsofeffectiveworkingmotivationand working satisfaction through income standard factor. Therefore, there must be a revision ofmodeloncorrelationalvariablesassumedinthisresearch.